2019
DOI: 10.1111/are.14075
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of growth and reproduction performance of broodstock Pacific white shrimp Litopenaeus vannamei reared in oceanic and brackish water

Abstract: This study provides a preliminary evaluation of feasibility of brackish water breeding. Shrimps were initially cultured at brackish water. Shrimps were reared at different stages (5, 6, 7 and 8 months, respectively), and 300 female shrimps were selected from each stage for growth at an enhanced salinity of 30 ppt. When the shrimps were sexually mature, the reproductive characteristics (mating rate, egg number and nauplii number) of the broodstock shrimps, quality of nauplii (malformation rate of nauplii) and q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
2
0
0
Order By: Relevance
“…In this study, the heritability estimates (Cardellino and Rovira 1987) of growth traits at different ages were 0.256 ± 0.119 to 0.441 ± 0.124. The results are consistent with heritability estimates in prior studies (Hernandez-Ruiz et al 2020;Perez-Rostro and Ibarra 2003;Sui et al 2016) and our previous studies (Yuan et al 2018;Zhang et al 2017a, b) but lower than those reported by others (Andriantahina et al 2012;Ren et al 2020;Tan et al 2019). The difference might be caused by genetic or environmental factors, such as use of different populations, growth conditions, ages, sexes, and models (Elvingson and Johansson 1993;Korkeila et al 1991;Lu et al 2016;Montaldo et al 2013;Zhang et al 2017a).…”
Section: Heritability Of Growth and Multiple-stress Conditions Traitssupporting
confidence: 91%
“…In this study, the heritability estimates (Cardellino and Rovira 1987) of growth traits at different ages were 0.256 ± 0.119 to 0.441 ± 0.124. The results are consistent with heritability estimates in prior studies (Hernandez-Ruiz et al 2020;Perez-Rostro and Ibarra 2003;Sui et al 2016) and our previous studies (Yuan et al 2018;Zhang et al 2017a, b) but lower than those reported by others (Andriantahina et al 2012;Ren et al 2020;Tan et al 2019). The difference might be caused by genetic or environmental factors, such as use of different populations, growth conditions, ages, sexes, and models (Elvingson and Johansson 1993;Korkeila et al 1991;Lu et al 2016;Montaldo et al 2013;Zhang et al 2017a).…”
Section: Heritability Of Growth and Multiple-stress Conditions Traitssupporting
confidence: 91%
“…Moreover, all farmers agreed with the concept of maintaining appropriate stocking density of shrimp larvae, since this can impact upon shrimp quality. Consistent with previous studies, it was understood that rearing shrimp at high stocking densities can increase waste accumulation and causes low shrimp growth [33]. However, there were no statistical differences in farm management practices among groups of adopters when assessed by F-test.…”
Section: Farmers' Perceptions Of Gapsupporting
confidence: 86%